Changing living arrangements and stress during Covid-19 lockdown: Evidence from four birth cohorts in the UK - Maria Evandrou; Jane Falkingham; Min Qin; Athina Vlachantoni (Elsevier, 2021)
Background: The outbreak of Covid-19 in the UK has seen many families unexpectedly brought back together. The circumstances and stories of individual families have been picked up in the press focussing on the difficulties of people adjusting to their changed living arrangements. Yet, there have been few empirical analyses on how such changes might influence people's health and wellbeing. Therefore, this study explored the changing patterns of perceived stress by living arrangements change during the first wave of the Covid-19 pandemic in 2020. Methods: The data used relates to 12,532 cohort members in the special Covid-19 surveys conducted with the participants of the 1958, 1970, 2000-01 British birth cohorts and Next Steps (born in 1989-90) in May 2020. Probit regression models were used to assess the chance of reporting increased stress amongst those who had experienced changes in living arrangements during the pandemic compared to those who had not. Results: The results provide strong evidence that those individuals whose living arrangements changed during the Covid-19 pandemic have a higher likelihood of reported increased stress than those whose living arrangements remained unchanged. This was most clearly seen for older cohorts. Increased interpersonal conflict plays a role in mediating the association, especially for the younger cohort. Conclusions: The findings confirm that during the first lockdown, changing living arrangements were negatively associated with individuals' mental wellbeing. As prolonged periods of stress can lead to serious health problems and policymakers need to be mindful that services may need to take these new, albeit for many temporary, forms of living arrangements into account.